2019
DOI: 10.3389/fpsyg.2019.00633
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress: Relationship With Symptoms, Exhaustion, and Emotions Among Cemetery Workers

Abstract: Background: Cemeteries workers are deserving of attention because they are exposed to various psychosocial risks: these workers are subject to painful contacts and daily exposed to a work content linked to death experiences and the emotions associated with them. Secondary trauma develops from this continuous contact with others’ suffering; operators working with this type of traumatic content and dynamic could suffer from emotional disorders ( Figley, 1995 ). Therefore, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…The link between STS and PTSD-symptoms among aid-workers is understudied. Associations between STS, trauma exposure, anxiety and depression (Colombo, Emanuel, & Zito, 2019;Gärtner, Behnke, Conrad, Kolassa, & Rojas, 2019) with an additional association to PTSD-symptoms and work stressors (Griffiths, Royse, & Walker, 2018) have been observed. Trauma exposure has been associated with pain and physical health problems (D'Andrea, Sharma, Zelechoski, & Spinazzola, 2011;Pérez, Abrams, López-Martínez, & Asmundson, 2012).…”
Section: Sts and Its Negative Associationsmentioning
confidence: 91%
See 2 more Smart Citations
“…The link between STS and PTSD-symptoms among aid-workers is understudied. Associations between STS, trauma exposure, anxiety and depression (Colombo, Emanuel, & Zito, 2019;Gärtner, Behnke, Conrad, Kolassa, & Rojas, 2019) with an additional association to PTSD-symptoms and work stressors (Griffiths, Royse, & Walker, 2018) have been observed. Trauma exposure has been associated with pain and physical health problems (D'Andrea, Sharma, Zelechoski, & Spinazzola, 2011;Pérez, Abrams, López-Martínez, & Asmundson, 2012).…”
Section: Sts and Its Negative Associationsmentioning
confidence: 91%
“…Trauma exposure has been associated with pain and physical health problems (D'Andrea, Sharma, Zelechoski, & Spinazzola, 2011;Pérez, Abrams, López-Martínez, & Asmundson, 2012). STS and exposure to trauma clients has been associated with fatigue, insomnia, joint/muscular pain, gastritis, headaches, and respiratory difficulties (Colombo et al, 2019). STS mediated the associations between exposure to trauma and perceived physical health (Lee, Gottfried, & Bride, 2018).…”
Section: Sts and Its Negative Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the few studies that have been interested in assessing the quality of working life of this peculiar working population, only a small number have assessed how the psychosocial factors of the funeral context can specifically impact burnout levels [ 8 ]. This is surprising since, among other mental health issues such as depression, death anxiety and post- and secondary-traumatic stress disorder that have been more extensively analyzed [ 9 , 10 , 11 , 12 , 13 , 14 ], funeral and mortuary workers, due to their work environment, are more likely to suffer from compassion fatigue and burnout [ 15 , 16 , 17 ], which in turn may leave to deleterious consequences for their health-related behaviors and impaired work ability [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that organizational stressors have a higher impact on PTSD than operational stressors (Maguen et al, 2009). The consequences of organizational demands could have an impact on the development of STS in POs as well as in other workers (Colombo et al, 2019). An investigation conducted by Sharma (2013) showed that hostile relationships between supervisors and workers negatively affect work performance, stress perception and its consequences; these findings were consistent with previous research (Chopko, 2010;Shane, 2010;Yuan et al, 2011) that found that the management of potentially traumatic events leads to a decrease in psychological problems among traumatized POs.…”
Section: Sts and The Job Demands-resources Modelmentioning
confidence: 99%